2008
DOI: 10.2478/v10003-008-0004-y
|View full text |Cite
|
Sign up to set email alerts
|

ESR Dating of Sedimentary Quartz from Two Pleistocene Deposits Using Al and Ti-Centers

Abstract: One sample from a fluvial terrace of Loir river (France) deposited during isotopic stages 7-8 and two samples from isotopic stage 5 marine sediments of Echizen Coast (Japan) were dated by ESR of quartz grains. Both additive and regenerative techniques were used on Ti-Li and Ti-H centers of quartz. No change of sensitivity of the centers was observed during regeneration which significantly reduced the errors on the equivalent doses. Bleaching experiments indicated that the Ti-Li center is less sensitive to UV(u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 16 publications
1
27
0
4
Order By: Relevance
“…A total of seven bulk samples was collected from silt-sized deposits of fluvial terraces and karst caves along the Suoxi River valley, as well as the adjacent Maoxi River. The geochronology of terrace and karst cave deposits was established by means of thermoluminescence (TL) and electron spin resonance (ESR) analyses based on previous publications (Forman 1989;Laurent et al 1998;Chiavari et al 2001;Wray et al 2001;Tissoux et al 2008). Two quartz-rich samples were selected from the highest terrace and karst cave level for ESR dating, and five quartz-rich samples were collected from lower terrace levels for TL dating, respectively ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A total of seven bulk samples was collected from silt-sized deposits of fluvial terraces and karst caves along the Suoxi River valley, as well as the adjacent Maoxi River. The geochronology of terrace and karst cave deposits was established by means of thermoluminescence (TL) and electron spin resonance (ESR) analyses based on previous publications (Forman 1989;Laurent et al 1998;Chiavari et al 2001;Wray et al 2001;Tissoux et al 2008). Two quartz-rich samples were selected from the highest terrace and karst cave level for ESR dating, and five quartz-rich samples were collected from lower terrace levels for TL dating, respectively ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Voinchet et al, 2007Voinchet et al, , 2010Tissoux et al, 2008;Liu et al, 2010Liu et al, , 2013aLiu et al, , 2013bLiu et al, , 2014. In such sediment, the size of the grain varies from few micron meter to few centimeters, and the sensitivities of both ESR and OSL signals of the quartz showed strong grain size depended effects (Buhay et al, 1988;Pietsch et al, 2008;Fan et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Bleaching experiments have shown that the Ti centre can be completely bleached after the equivalent of a few days of sunlight exposure (Toyoda et al, 2000;Tissoux et al, , 2008Gao et al, 2009). Considering that optical dating of river sediments requires bleaching times in the second to minute range for complete bleaching and as incomplete bleaching is a serious problems in geological context (Olley et al, 2004), one would expect that ESR dating results on river sediments could be severely overestimated.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, improvements in the understanding of the bleaching mechanism on the quartz ESR signals resetting, have confirmed the potential of dating bleached quartz by ESR. Sunlight exposure was initially considered as the first driver for quartz bleaching in fluvial sediments and several experiments claimed that the Ti-Li centre can be completely bleached after the equivalent of a few days of sunlight exposure (Toyoda et al, 2000;Tissoux et al, 2007Tissoux et al, , 2008Gao et al, 2009) while the Al centre can only be bleached to a stable residual level (varying from one sample to another) after natural sunlight exposure of 2-4 months or perhaps even 6 months (Voinchet et al, 2003). Fieldwork realized by Voinchet et al (2007) led them to claim that the Ti-Li centre of quartz extracted from river sediments can be completely reset and the Al centre could be reduced to a stable level only after 1 km of transport in natural presentday conditions.…”
Section: Resultsmentioning
confidence: 99%